Optimizing Teacher Creativity: The Role of Local Wisdom and Organizational Support - Nugraha, Mohammad Lutfi; Hardhienata, Soewarto; Hidayat, Rais (Journal La Edusci, 2025)
This study develops a model for enhancing early childhood education (ECE) teacher creativity based on local wisdom and organizational support in Tasikmalaya, Indonesia. Using path analysis and SITOREM methodology, the research examines direct and mediated effects among 160 ECE teachers selected through simple random sampling. Findings reveal that local wisdom significantly influences teacher creativity both directly (β = 0.52, p < 0.001) and indirectly through organizational support (β = 0.23, p < 0.01), with a total effect of β = 0.75. Organizational support demonstrates substantial direct effects (β = 0.41, p < 0.001), particularly through leadership encouragement, collaborative environments, and resource provision. The SITOREM analysis categorizes 28 indicators into four quadrants, identifying seven high-performing indicators to maintain (including traditional games integration, M = 4.12) and twelve requiring priority improvement. The three most critical gaps are: use of local arts as learning media (β = 0.44, M = 2.31), collaborative opportunities in culture-based learning design (β = 0.41, M = 2.45), and incentive systems for innovation (β = 0.39, M = 2.18). Key barriers include teacher confidence deficits in traditional arts (67%), resource limitations, and time constraints. The study proposes a three-tier implementation framework addressing institutional foundations, professional development, and systemic quality enhancement, differentiated by school resource levels, principal cultural competency, and teacher experience. Results underscore the need for contextual teacher development integrating cultural values with organizational reform. The study offers evidence-based strategies for fostering culturally-rooted teacher innovation in organizationally supportive environments.